Reabilitação auditiva na criança: a questão da adesão ao tratamento e ao uso do aparelho de amplificação sonora individual - Miguel, Juliana Habiro de Souza (2010)
Introduction: Early diagnosis of hearing loss in children, as well as fast intervention, have been shown to be determining factors for hearing and language development, with important implications for the social inclusion process and communicative performance. However, intervention success is directly related to the parents adhesion to the Hearing Care Service, understanding of choices, and potential of their children, in order to adjust their expectations during the treatment. The present study aims to analyze alternatives that guarantee adhesion to use of Hearing Aids, and greater family participation in the initial steps of the intervention. Goal: Discuss family adhesion to the initial part of the intervention, regarding hearing aid usage and participation in the process, as well as its link with hearing and language performance of hearing impaired children. It also aims to examine how adhesion-related issues are problematized in the Family Adhesion Group (GrAF). Method: The study comprehended parents / caregivers of 16 hearing impaired children who attended the ADAPTI (Hearing Aid Fitting and Initial Therapy) in 2009, who had formally applied for the Hearing Care Service (Centro Audição na Criança CeAC). The parents were divided in three groups: Previously Determined (Families that attend both the speech therapy and the GrAF, from the first day set for the beginning of sessions, to the last day); Continuous Flow (Families that started attending the group from the moment they arrived at the CeAC for the ADAPTI); and Control (Families that only attended speech therapy, but not the GrAF). The instruments used included: registering the information from the charts of subjects involved in the research, interviews with the parents (NOVAES, 1986), Family Involvement Scale Evaluation (MOELLER, 2000), MUSS, IT MAIS, cultural awareness activities (NOVAES, 1986) and effective hearing aid usage evaluation. Outcomes: The study verified the effectiveness of parent adhesion to their children s treatment, with over 50% of attendance in the proposed activities (therapeutic intervention and / or GrAF). Regarding the operation and the activities performed at the GrAFs, it was possible to evaluate the differences concerning ties and experience exchanges among the participants. The statistical analysis of children groups, internally homogeneous and heterogeneous among themselves regarding the variables: IT MAIS and MUSS, it was possible to establish three distinct groups regarding datalog usage (hours a day), family participation and degree of hearing loss. Conclusion: The systematic use of hearing aids was the only variable closely related to hearing and language skills. Degree of hearing loss and age at the beginning of amplification, have not explained the development of the children in the study. Establishing routines and procedures at the Hearing Care Services to evaluate adhesion of hearing impaired children s families to the treatment, at the beginning of the intervention are essential, especially concerning the use of hearing aids and participation in the hearing rehabilitation process